Aeroelastic Control of a Wind Turbine Blade Using Microtabs Based on UA97W300-10 Airfoil. Issue 5 (October 2013) - Li, N.; Balas, M. J.
The unsteady flow over a rotating wind turbine blade is described by the Beddoes-Leishman dynamic stall model. Based on the asymmetric airfoil UA97W300-10, a wind turbine blade section with unsteady aerodynamic loads is modeled as an aeroelastic system for this vibration suppression study. Aeroelastic stability of the system is analyzed by open-loop tests to identify the flutter speed. With consideration of wind turbine operations, control strategies for flutter suppression are made separately in each operation region and implemented by a designed Adaptive Controller using microtab devices, which are positioned at the trailing edge of the airfoil with deployment at the maximum height of 5% of chord length. The control effects of the Adaptive Control and microtabs are investigated by closed-loop tests. The stability of the Adaptive Controller is proved using a new Adaptive Stability Theorem, which is also illustrated by examples.